2006
DOI: 10.1016/j.jcrs.2006.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Visual performance of aspherical and spherical intraocular lenses: Intraindividual comparison of visual acuity, contrast sensitivity, and higher-order aberrations

Abstract: Although Z(4)(0) was significantly lower in the eyes with the aspherical IOL, no statistically significant differences were found between aspherical and spherical IOLs in LCVA, HCVA, and contrast sensitivity. Statistical analysis of intraindividual contrast sensitivity differences showed that in most patients, this Z(4)(0) difference was too low to have an effect on contrast sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
2
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 38 publications
(42 reference statements)
5
62
2
5
Order By: Relevance
“…6 Both in the laboratory by using adaptive optics 3 and in clinical studies, aspheric IOLs have been shown to reduce ocular SAs, improve contrast sensitivity, and improve night driving performance. 2,4 However, 2 recent studies 13,14 reported no differences between aspheric and spherical IOLs in low-contrast visual acuity, high-contrast visual acuity, and contrast sensitivity. Although multiple factors may contribute to these conflicting findings, lack of optimization of residual ocular SA might play a role.…”
Section: Discussionmentioning
confidence: 99%
“…6 Both in the laboratory by using adaptive optics 3 and in clinical studies, aspheric IOLs have been shown to reduce ocular SAs, improve contrast sensitivity, and improve night driving performance. 2,4 However, 2 recent studies 13,14 reported no differences between aspheric and spherical IOLs in low-contrast visual acuity, high-contrast visual acuity, and contrast sensitivity. Although multiple factors may contribute to these conflicting findings, lack of optimization of residual ocular SA might play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the slow release of aqueous humor prevented abrupt shallowness of the anterior chamber and a resulting sudden change in IOP. Additional important advantages of controlling the flow of aqueous humor and controlling IOP include avoiding lens and iris damage, choroidal hemorrhage or effusion, and decompensation retinopathy [19][20][21][22][23][24]. None of these complications were observed in our series.…”
Section: Discussionmentioning
confidence: 90%
“…One study found no significant difference in contrast sensitivity between spherical and aspheric lenses after three to four months. 52 Other studies have reported significant improvement in contrast sensitivity, 53,54 without a reduction in pseudo-accommodative amplitude. 55 A reduction in the depth of focus that can result from asphericity is an important consideration as most patients undergoing cataract surgery are presbyopic.…”
Section: Aspheric Lensesmentioning
confidence: 95%